2021
DOI: 10.1016/j.ejro.2021.100325
|View full text |Cite
|
Sign up to set email alerts
|

Etiological profile and main imaging findings in patients with granulomatous diseases who underwent lung biopsy

Abstract: Background: Granulomatous Lung Diseases (GLD) encompasses a wide range of infectious and non-infectious conditions characterized by chronic inflammatory response. However, different GLD may share similar imaging findings. In this context, the purpose of this study was to outline the etiological profile and their imaging features in patients with GLD who underwent lung biopsy. Methods: Patients with granulomatous lesions in lung biopsies and previous chest CT performed from 2014 to 2017 at our institution had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Due to the lack of specificity of clinical symptoms, lung imaging is the primary method for diagnosing tuberculosis with lung cancer and uncomplicated tuberculosis. 16 This study’s chi-square test results showed that tuberculosis combined with lung cancer group had fewer calcifications, streak shadows, speckle shadows, and cavitation signs than the pulmonary tuberculosis group.…”
Section: Discussionmentioning
confidence: 72%
“…Due to the lack of specificity of clinical symptoms, lung imaging is the primary method for diagnosing tuberculosis with lung cancer and uncomplicated tuberculosis. 16 This study’s chi-square test results showed that tuberculosis combined with lung cancer group had fewer calcifications, streak shadows, speckle shadows, and cavitation signs than the pulmonary tuberculosis group.…”
Section: Discussionmentioning
confidence: 72%
“…These concomitant lesions are usually seen as incomplete absorption of chronic inflammatory or infectious diseases, thus their existence and diffuse distribution frequently indicates a potential condition of easily suffering inflammation and infection. 17 , 24 In contrast, only patchy GGO or consolidation in the same lobe and ipsilateral lung were more commonly detected in patients with non-neoplastic GGNs. The occurrence of patchy GGO or consolidation seems more closely associated with target GGNs, probably because they are concurrent lesions, and most of non-neoplastic GGNs, patchy GGO, or consolidation were usually seen as active inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…This presentation differs from that of immunocompetent patients, in whom histoplasmosis most often presents as solitary or few nodules, sometimes calcified [ 28 , 31 , 32 ]. In our immunocompromised patients, nodules, present in > 30% were the second most frequent abnormality, and were associated with miliary micronodules in one patient.…”
Section: Discussionmentioning
confidence: 99%